A systematic literature review of explainable risk assessment models for bronchial asthma - Cessie Valenie, Edwin; Phei Chin, Lim; Dayang Nurfatimah, Awang Iskandar; Diana Ng, Leh Ching (AME Publishing Company, 2026)
Background: The reduced quality and risks to life brought on by bronchial asthma (BA) have heightened the need for trustworthy risk assessment solutions with deliberate interpretability and transparency. Improper management of BA, such as ignoring symptoms, improper inhaler technique, or recent admissions to the intensive care unit (ICU), puts a patient at a higher risk of future asthma exacerbations, complications, or even death. This paper details a systematic literature review on recent literature to identify and analyse current explainable artificial intelligence (XAI) risk assessment models used in BA or the assessment of risk in healthcare using XAI.